2015
DOI: 10.1089/omi.2014.0099
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analyses ofBacillus subtilisafter Treatment with Plumbagin, a Plant-Derived Naphthoquinone

Abstract: Infectious diseases and increasing antibiotic resistance among diverse classes of microbes are global health concerns and a prime focus of omics systems science applications in novel drug discovery. Plumbagin is a plant-derived naphthoquinone, a natural product that exhibits antibacterial activity against gram-positive bacteria. In the present study, we investigated the antimicrobial effects of plumbagin against Bacillus subtilis using two complementary proteomics techniques: two-dimensional electrophoresis (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…50S ribosomal protein L10 (spot 15, 16) and 30S ribosomal protein S2 (spot 10) are structural constituents of ribosomes and participate in the translation process, and they were upregulated in the treatment group. Similar results were obtained in a previous study [8], which reported that 30S and 50S ribosomerelated proteins were upregulated in B. subtilis following treatment with plumbagin, a structural analog of juglone. We speculate that these proteins may participate in the synthesis of stress responserelated factors that are expressed in response to drug treatment.…”
Section: Annotation Of Molecular Function and Biological Processessupporting
confidence: 91%
“…50S ribosomal protein L10 (spot 15, 16) and 30S ribosomal protein S2 (spot 10) are structural constituents of ribosomes and participate in the translation process, and they were upregulated in the treatment group. Similar results were obtained in a previous study [8], which reported that 30S and 50S ribosomerelated proteins were upregulated in B. subtilis following treatment with plumbagin, a structural analog of juglone. We speculate that these proteins may participate in the synthesis of stress responserelated factors that are expressed in response to drug treatment.…”
Section: Annotation Of Molecular Function and Biological Processessupporting
confidence: 91%
“…We used the oxidative agent plumbagin to determine if poly(P) accumulation alters sensitivity to inhibitors of respiratory electron transport (38,68). The ppk2::Tn mutant was more sensitive than the wild type and the ppx1-deficient mutant to plumbagin, suggesting that ppk2 deficiency shifts bacteria to a greater dependence on the citric acid cycle and the electron transport chain (69). Furthermore, the ppx1-deficient mutant showed increased susceptibility to clofazimine, which destabilizes the bacterial membrane and targets the redox cycling pathway by enzymatic reduction of the drug by NDH-2, the primary respiratory chain NADH:quinone oxidoreductase of mycobacteria, and nonenzymatic oxidation of reduced clofazimine by O 2 , yielding reactive oxygen species (39,70).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that plumbagin blocks energy generation and also suppresses fatty acid biosynthesis. Repression of proteins directly linked to cell division (FTSA and SpoVG) was also observed (Reddy et al, 2015 ). Another example is the elucidation of the MOA for the alkaloid roemerine from Papaver rhoeas against E. coli , which was related to the inhibition of membrane permeability and sugar transporter proteins (Gokgoz and Akbulut, 2015 ).…”
Section: Proteomics Assaysmentioning
confidence: 93%